The Relationship Between Environmental Knowledge Levels and Environmental Care Attitudes Among Science Education Students at Makassar State University - Samputri, Salma; Nasrul, Nasrul; Arfandi, Arfandi; Mulkisam, Mutia; Syakirah, Adinda Triyana; Afni, Nur; Rasyid, Rasdyanti; Maru, Rosmini (LaGeografia, 2025)
The present study aims to examine the relationship between environmental knowledge and environmental care attitudes among students of the Science Education Study Program at Makassar State University. Understanding this relationship is essential not only for strengthening students’ ecological competencies but also for supporting the development of environmental education in higher education. This research employed a quantitative correlational design to determine the degree of association between the variables. Data were collected from students enrolled in the even semester of the 2022/2023 academic year using two instruments: a Likert-scale questionnaire to measure environmental care attitudes and a multiple-choice test to assess environmental knowledge. The sample was determined using the Slovin formula to ensure representativeness, and the data were analyzed in SPSS through descriptive analysis using frequency distributions and inferential analysis using Pearson’s product–moment correlation test. The results show that 80% of the students possess good environmental knowledge, and 82% exhibit good environmental care attitudes. The correlation test indicates a significant relationship between environmental knowledge and environmental care attitudes (p-value < 0.05), suggesting that higher levels of environmental knowledge are associated with stronger pro-environmental attitudes.